Armed forces and society
Armed Forces & Society (AFS), a quarterly publication, publishes articles on military institutions, civil-military relations, arms control and peacemaking, and conflict management. The journal is international in scope with a focus on historical, comparative, and interdisciplinary discourse. The editors and contributors include political scientists, sociologists, historians, psychologists, scholars, and economists, as well as specialists in military organization and strategy, arms control, and peacekeeping.